Pengaruh Pengalaman Kerja dan Motivasi Kerja terhadap Kinerja Karyawan dengan Melalui Kompetensi Kerja pada PT. Transco Energi Utama - Reski Sumariani; Marta Widian Sari; Selvi Zola Fenia (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to test how much influence financial knowledge and personality have on This research aims to examine the influence of work experience and work motivation on employee performance through job competence. The data collection method is through surveys and distributing questionnaires, with a sample of 57 respondents. The analytical method used is structural equation modeling using smartpls. The research of this study conclude that : (1) work experience influences work competency at PT. Transco Energi Utama. (2) work motivation has a negative and significant influence on work competence at PT. Transco Energi Utama. (3) work experience does not have a positive and significant effect on employee performance at PT. Transco Energi Utama. (4) work motivation does not have a positive and significant effect on employee performance at PT. Transco Energi Utama. (5) work competency has a positive and significant influence on employee performance at PT. Transco Energi Utama. (6) work experience has a negative and significant effect on employee performance through work competency at PT. Transco Utama Energi. (7) work motivation has a positive and significant effect on employee performance through work competency at PT. Transco Energi Utama.